2007
DOI: 10.5688/aj710353
|View full text |Cite
|
Sign up to set email alerts
|

Integration of an Internet-based Medical Chart Into a Pharmacotherapy Lecture Series

Abstract: Objectives. To integrate an Internet-based medical chart (IMC) system into a pharmacotherapy course to facilitate evaluation and feedback processes, foster development of written documentation skills, and prepare pharmacy students for future changes in electronic medical documentation systems.Design. An IMC system was introduced into a pharmacotherapy course for third-professional year pharmacy students and 4 ''finish the SOAP note'' activities were added to the curriculum. Students' performance on the SOAP no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 2 publications
0
37
0
Order By: Relevance
“…Brown and colleagues observed that lower quality assessment and plan sections were seen on the first note (54% needed improvement), although that improved with each successive attempt (27% needed improvement by the fourth note, p<.001), and errors in assessment occurred twice as often as in the plan section (20.5% vs. 10.5% of notes, respectively) of the SOAP note. 5 Other studies have also noted that assessment documentation is more often incomplete versus other sections of the note. 7,16 The findings of our study A J P E A c c e p t e d D r a f t align with early curriculum studies in which students consistently struggled with the assessment sections, but that repeated SOAP note writing opportunities improved students' confidence and abilities.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Brown and colleagues observed that lower quality assessment and plan sections were seen on the first note (54% needed improvement), although that improved with each successive attempt (27% needed improvement by the fourth note, p<.001), and errors in assessment occurred twice as often as in the plan section (20.5% vs. 10.5% of notes, respectively) of the SOAP note. 5 Other studies have also noted that assessment documentation is more often incomplete versus other sections of the note. 7,16 The findings of our study A J P E A c c e p t e d D r a f t align with early curriculum studies in which students consistently struggled with the assessment sections, but that repeated SOAP note writing opportunities improved students' confidence and abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Brown, et al's incorporation of the SOAP note format during a third-year pharmacotherapy course showed that overall mean SOAP note scores improved from 3.23 to 3.62 (out of 4) from the first to the fourth note (p<.001). 5 Students consistently struggle with proper assessment of patient care goals. On each SOAP note, the lowest scores seen were in the assessment section, which is consistent with other studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations